The Conception of Computer Networking Based on Personnel Management and Human Resources Development. Issue 3 (August 2021) - Yang, Yalin
Abstract: With the progress of the society and the development of science and technology, the computer is widely used in people's life, the computer is not only convenient for people's life, but also widely used in many enterprises personnel information management. In this article, application of computer slowly into the center of the personnel management has made the corresponding explanation, and the personnel management of relevant enterprises also made the corresponding elaboration, and on the knowledge management system to make the corresponding ideas and guess research, computer technology is applied to the personnel management has greatly increased the efficiency of the relevant enterprises, but also save a lot of manpower material resources, it also has a great significance to enterprise's development, at the same time, closer to a push the development of the enterprise, improve the working efficiency.